the PENGARUH PRODUCT QUALITY AND PRICE TERHADAP KEPUTUSAN PEMBELIAN PRODUK BODY LOTION SCARLETT WHITENING : (Studi Kasus Pengguna Body Lotion Scarlett Whitening di Indonesia) - Listiya, Marcella Tirta; Wardhana, Aditya (FEB Universitas Sam Ratulangi Manado, 2024)
Indonesian people tend to have dry and dull skin due to the higher intensity of sun exposure in the tropical season. Several cities in Indonesia have unhealthy air quality. Gray air is a sign of unhealthy air quality. Consumers must be careful of unwanted things, such as products that do not include BPOM. When consumers feel a need for the goods to be purchased, they begin to make purchasing decisions. The purpose of this research is to understand and evaluate the extent of the impact of product quality on the decision to purchase Scarlett Whitening body lotion, to understand and evaluate the extent of the impact of price on the decision to purchase Scarlett Whitening body lotion products, to assess the extent of the joint impact of product quality and price on the decision purchase Scarlett Whitening body lotion products.This study used quantitative methods and a Cochran sample, with a total of 153 respondents. This study also used questionnaire analysis and literature review. The data analysis techniques used in this research are causal analysis and multiple linear analysis. Conclusions are drawn regarding the relationship between product quality and purchasing decisions based on t count 3.028 and t table 1.984. The results obtained by Ha1 indicate that product quality has a quite significant positive influence on purchasing decisions. This hypothesis can be accepted at the significance level of 0.003. The influence that the price variable has on purchasing decisions can be identified by the calculated t value which exceeds the t table value, namely 7.771 ≥ 1.984. Therefore, it can be concluded that Ha2 is accepted, indicating that there is a significant positive influence of price on purchasing decisions partially. These results support the second hypothesis, which can be accepted with a significance level of 0.000. The influence between product quality and price variables on purchasing decisions reached a percentage of 53.5%, while the remaining 46.5% was influenced by other variables not included in this research. The F test results show that the two variables, namely product quality and price, together have a significant effect of 0.000 ≤ 0.05 and the calculated F value is 86.217 F table, namely 3.07. Thus, it can be concluded that product quality and price together have a significant influence on purchasing decisions for Scarlett Whitening body lotion products.